2012
DOI: 10.1038/onc.2012.297
|View full text |Cite
|
Sign up to set email alerts
|

The histone methyltransferase MMSET/WHSC1 activates TWIST1 to promote an epithelial–mesenchymal transition and invasive properties of prostate cancer

Abstract: Epigenetic deregulation of gene expression plays a role in the initiation and progression of prostate cancer (PCa). The histone methyltransferase MMSET/WHSC1 (Multiple Myeloma Set Domain) is overexpressed in a number of metastatic tumors, but its mechanism of action has not been defined. In this work, we found that PCa cell lines expressed significantly higher levels of MMSET compared to immortalized, non-transformed prostate cells. Knockdown experiments showed that, in metastatic PCa cell lines, dimethylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
115
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 51 publications
7
115
1
Order By: Relevance
“…Transcriptionally, TWIST1 can be regulated by miRNAs and transcription factors such as HMGA2, KLF17, and STAT3 (24)(25)(26)(27). Epigenetic modifications, including DNA and histone methylation, also play roles in the activation of TWIST1 expression (28,29). However, the regulation of the histone acetylation status of TWIST1 has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptionally, TWIST1 can be regulated by miRNAs and transcription factors such as HMGA2, KLF17, and STAT3 (24)(25)(26)(27). Epigenetic modifications, including DNA and histone methylation, also play roles in the activation of TWIST1 expression (28,29). However, the regulation of the histone acetylation status of TWIST1 has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer for example, the EZH2/NSD2 axis confers increased cell proliferation, migration, invasion, stem cell-like properties and tumor growth in a mouse xenograft model [66]. Further studies in prostate cancer have shown that NSD2 acts as a co-activator with NF-κB and androgen receptor [67,68], and regulates the epithelial to mesenchymal transition by dimethylating H3K36 at the TWIST1 locus and activating TWIST1 expression [69].NSD3: frequently overexpressed in diverse tumor types NSD3, also known as WHSC1L1, is overexpressed in cancer [70] and catalyzes mono-and di-methylation at H3K36 in vitro [71]. In cells NSD3 functions as a transcriptional activator, but NSD3's KMTase activity may contribute only partially to its geneactivating role.…”
mentioning
confidence: 99%
“…In prostate cancer for example, the EZH2/NSD2 axis confers increased cell proliferation, migration, invasion, stem cell-like properties and tumor growth in a mouse xenograft model [66]. Further studies in prostate cancer have shown that NSD2 acts as a co-activator with NF-κB and androgen receptor [67,68], and regulates the epithelial to mesenchymal transition by dimethylating H3K36 at the TWIST1 locus and activating TWIST1 expression [69].…”
mentioning
confidence: 99%
“…The NSD proteins are oncogenes highly expressed in numerous pathological conditions and are considered attractive novel therapeutic targets in cancers [2,[9][10][11][12][13][14][15][16][17][18][19][20]. The amplification of NSD1 has been reported in multiple myeloma, lung cancer, neuroblastoma and glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the inhibition of NSD members by small molecules represents a valuable therapeutic strategy in several human cancers where elevated levels of NSD members have been reported [2,4,5,12,14,17,18,26,32,33,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%